2010
DOI: 10.1002/cncr.25373
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic esophageal tumor length

Abstract: BACKGROUND: Pathologic esophageal tumor length (pL) is an independent predictor of long-term survival. However, whether patients with longer (high-risk) tumors can be identified by endoscopy before surgery has not been established. The objective of the current study was to determine the value of endoscopically measured tumor length (cL) in predicting overall survival in patients with esophageal adenocarcinoma. METHODS: All patients with esophageal adenocarcinoma who had undergone resection without neoadjuvant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 50 publications
2
17
1
Order By: Relevance
“…As previous reports reported that 30 mm was a well separation [3-6], we used this length to evaluate survival time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As previous reports reported that 30 mm was a well separation [3-6], we used this length to evaluate survival time.…”
Section: Resultsmentioning
confidence: 99%
“…Recent publications have suggested that pathologic esophageal tumor length is directly correlated with long-term survival [3-6]; however, most of these data originated in western countries, and the cancer type was predominantly adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Francisco and Agoston et al [30, 31] declared that the relationship between the size of the oncologic entity with a worse prognosis in esophageal adenocarcinoma was not proven. In a retrospective study of 273 patients at the University of Texas MD Anderson Cancer Center and the University of Rochester Medical Center, Gaur et al [32] identified tumor size as an independent prognostic indicator and demonstrated that an endoscopically measured tumor length >2 cm predicted a decline in long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…This was found to be 3.1 cm ( Figure S1A) -based on the highest Youden index (sensitivity + specificity -1) (Heagerty et al 2000). Then, we used a regression tree survival analyses for pathologically measured tumor length (Gaur et al 2011) and found it to be 2.9 cm ( Figure S1B). The mean of these two results -3.0 cm -was used as the threshold value for optimal cut-off.…”
Section: Statistical Analysesmentioning
confidence: 94%
“…In the current American Joint Committee on Cancer (AJCC) staging system for esophageal tumors, stage depends on the depth of the tumor (T classification), lymph node involvement (N classification), and distant metastasis (M classification), without consideration on tumor length (Edge & Compton 2010). Studies have shown that pathologic tumor length had prognostic value to EAC (Bolton et al 2009;Gaur et al 2011;Yendamuri et al 2009). In China, a few studies were conducted to show the association between the overall survival (OS) rate and the tumor length, among the survival of ESCC patients (Feng et al 2013;Ma et al 2015;Wang et al 2011;Wang et al 2012).…”
Section: Introductionmentioning
confidence: 99%